2017
DOI: 10.1007/s10103-017-2193-y
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic inactivation of Paracoccidioides brasiliensis helps the outcome of oral paracoccidiodomycosis

Abstract: The antifungal drug therapy often employed to treat paracoccidiodomycosis (PCM), an important neglected fungal systemic infection, leads to offensive adverse effects, besides being very long-lasting. In addition, PCM compromises the oral health of patients by leading to oral lesions that are very painful and disabling. In that way, photodynamic therapy (PDT) arises as a new promising adjuvant treatment for inactivating Paracoccidioides brasiliensis (Pb), the responsible fungus for PCM, and also for helping the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…However, in the studies included in our review, several antifungals were reported to be effective in the treatment of different clinical forms of the disease, including azole derivatives, sulfonamide derivatives, and amphotericin B. Recently, experimental studies and case reports have revealed that photodynamic therapy can be an ancillary tool in the management of oral PCM, as it presents promising results in terms of accelerating the repair process and providing decontamination, progressively improving wound healing ( 29 , 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, in the studies included in our review, several antifungals were reported to be effective in the treatment of different clinical forms of the disease, including azole derivatives, sulfonamide derivatives, and amphotericin B. Recently, experimental studies and case reports have revealed that photodynamic therapy can be an ancillary tool in the management of oral PCM, as it presents promising results in terms of accelerating the repair process and providing decontamination, progressively improving wound healing ( 29 , 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of PDT was demonstrated in recent clinical research on periopathogens, [36][37][38] carious bacteria, 39,40 onychomycosis, 41,42 and paracoccidiodomycosis. 43 Antiviral therapy using laser light, known as photodynamic inactivation (PDI), is based on the same mechanisms as photodynamic antimicrobial chemotherapy (PACT), i.e., non-thermal viral inactivation. We can differentiate 2 types of virus structural damage caused by light -type I and type II photoreactions.…”
Section: Lasers Enhancing Chemical Reactionsmentioning
confidence: 99%
“…Until now, aPDT has been utilized for the disinfection of blood products, especially the inactivation of virus in frozen plasma [36–42]. In addition, it is especially useful for the treatment of infections in the mouth (oral), orthopedics, and dermatology [34,43–48].…”
Section: Recent Patents On Light-based Anti-infective Approachesmentioning
confidence: 99%